Synthetic modulation of ROS scavenging during host—Sclerotinia sclerotiorum interaction: a new strategy for the development of highly resistant plants - Yijuan Ding; Baoqin Yan; Siqi Zhao; Yangui Chen; Huafang Wan; Wei Qian (Phytopathology Research, 2024)
Abstract Sclerotinia sclerotiorum is a widespread fungal pathogen responsible for significant crop losses across the globe. The challenge of breeding resistant varieties is exacerbated by the fungus's sophisticated pathogenic mechanisms. A pivotal factor in the host-pathogen interaction is the regulation of reactive oxygen species (ROS) within both the fungi and the host plants. However, there is currently no efficient strategy to leverage this interaction mechanism for developing disease-resistant crop varieties. Here, we introduce an engineered ROS scavenging system designated as syn-ROS for impairing ROS neutralization in S. sclerotiorum while concurrently fortifying it in the host. The syn-ROS system comprises gene silencing constructs targeting the S. sclerotiorum Cu/Zn superoxide dismutase (SsSOD) and its copper chaperone (SsCCS), alongside overexpression constructs for the Arabidopsis thaliana AtSOD1 and AtCCS. Transgenic plants carrying the syn-ROS system demonstrated a marked enhancement in resistance to S. sclerotiorum. Upon infection, the expression of SsSOD and SsCCS was reduced, while the expression of AtSOD1 and AtCCS was enhanced in syn-ROS transgenic plants. Moreover, the infected syn-ROS plants showed decreased Cu/Zn SOD enzyme activity and elevated ROS concentrations within the fungal cells. In contrast, the cells of A. thaliana manifested increased Cu/Zn SOD enzyme activity and lowered ROS levels. Collectively, these findings suggest a novel and promising approach for contriving plants with robust resistance by synthetically manipulating ROS scavenging activities in the interaction between the host and S. sclerotiorum.